Memahami Indeks Persepsi Korupsi (IPK) Indonesia Dan Kontribusi Polisi Militer Untuk Meningkatkan IPK - Heryadi, Adi; Tarigan, Ilham B; Astuti, Weni (DHARMA BAKTI, 2022)
Indonesia's Corruption Perceptions Index score in 2020 is a reflection of public perceptionsthat were the object of the survey during 2020. Data released by Transparency InternationalIndonesia in January 2021 placed Indonesia with a GPA score of 37/100, down 3 points from2019 which was 40/100. From the various aspects surveyed, some have decreased and somehave stagnated. World Justice Project-Rule Of Law Index, which is an indicator thatmeasures public authority in the executive, legislative, and police/military (Suyatmiko(2021) is a score that has increased. Indonesia's corruption perception index score 2020 andhow the contribution of the Military Police contributes to boost the score Indonesian GPAfor the honor and honor of the nation in the eyes of the international community Serviceactivities will be held on December 28, 2021 at the Denpom IV/2 Yogyakarta HeadquartersJalan Magelang KM 5.5 Mlati, Sleman, DIY. Participants in this activity are 20 (twenty)members of Denpom IV /2 Yogyakarta from the enlisted, non-commissioned, to officer levels.However, 19 participants followed through to the end of the evaluation and evaluationactivities using the lecture and discussion method. It was found that 53% of participantsreally understood the material on the Indonesian Corruption Perception Index, as many as37% quite understood and do not understand 10%. Participants are also able to helpunderstand as members of the Military Police to improve their p increase in GPA scores fromcarrying out main tasks and as a member of the Police.